Sport injuries and illnesses during the first Winter Youth Olympic Games 2012 in Innsbruck, Austria - Ruedl, G.; Schobersberger, W.; Pocecco, E.; Blank, C.; Engebretsen, L.; Soligard, T.; Steffen, K.; Kopp, M.; Burtscher, M. (British Journal of Sports Medicine, 2012)
Background: Data on the injury and illness risk among young elite athletes are of utmost importance, because injuries and illnesses can counter the beneficial effects of sports participation at a young age, if children or adolescents are unable to continue to participate because of residual effects of injury or chronic illness. Objective To analyse the frequencies and characteristics of injuries and illnesses during the 2012 Innsbruck Winter Youth Olympic Games (IYOG). Methods: We employed the International Olympic Committee (IOC) injury surveillance system for multisport events, which was updated for the Winter Olympic Games in Vancouver 2010. All National Olympic Committees (NOCs) were asked to report the daily occurrence (or non-occurrence) of newly sustained injuries and illnesses on a standardised reporting form. In addition, information on athletes treated for injuries and illnesses by the Local Organizing Committee medical services was retrieved from the medical centre at the Youth Olympic Village and from the University hospital in Innsbruck. Results: Among the 1021 registered athletes (45% women, 55% men) from 69 NOCs, a total of 111 injuries and 86 illnesses, during the IYOG, were reported, resulting in an incidence of 108.7 injuries and 84.2 illnesses per 1000 registered athletes, respectively. Injury frequency was highest in skiing in the halfpipe (44%) and snowboarding (halfpipe and slope style: 35%), followed by ski cross (17%), ice hockey (15%), alpine skiing (14%) and figure skating (12%), taking into account the respective number of participating athletes. Knee, pelvis, head, lower back and shoulders were the most common injury locations. About 60% of injuries occurred in competition and about 40% in training, respectively. In total, 32% of the injuries resulted in an absence from training or competition. With regard to illnesses, 11% of women and 6% of men suffered from an illness (RR=1.84 (95% CI 1.21 to 2.78), p=0.003). The respiratory system was affected most often (61%). Conclusions: Eleven per cent of the athletes suffered from an injury and 9% from illnesses, during the IYOG. The presented data constitute the basis for future analyses of injury mechanisms and associated risk factors in Olympic Winter sports, which, in turn, will be essential to develop and implement effective preventive strategies for young elite winter-sport athletes.